Epidemiological studies on target leaf spot of sorghum incited by Bipolaris sorghicola - and R.N. BUNKER, R. KATEWA, KUSUM MATHUR* (Indian Phytopathology, 2008)
The target leaf spot pathogen Bipolaris sorghicola of sorghum could infect only sorghum and Johnson grass out of the 11 graminaceous host tested. Though the disease readily developed on 14 to 49- days-old plants, 28-days old plants were highly susceptible. The frequency of recovery of the pathogen from seeds declined with increased storage time. The pathogen was also found to survive on infested debris in soil, its maximum recovery from the plant debris in soil was up to 3 months of crop harvesting. Weekly planting and inoculations showed a positive, significant correlation between the disease severity and maximum relative humidity.